Polarizing Mexico: The Impact of Liberalization Strategy / Growth, Employment and Equity: The Impact of the Economic Reforms in Latin America and the Caribbean - Robinson, Ian (Relations industrielles / Industrial Relations, 2002)
A review is presented of 2 books: 1. Polarizing Mexico: The Impact of Liberalization Strategy by Enrique Dussel Peters, and 2. Growth, Employment and Equity: The Impact of the Economic Reforms in Latin America and the Caribbean by Barbara Stallings and Wilson Peres.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Developing countries; Economic conditions; Economic policy; Economic reform; Foreign investment; Free enterprise; LDCs; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social conditions